SIMULATION OF TURBULENCE AS A «VORTEX BACKFILL» - L. E. Melamed; G. A. Filippov (Известия высших учебных заведений: Проблемы энергетики)
The new method of simulation and the turbulent flow research, based on representation about turbulence as a current through «vortex backfill» is offered. The method of local fluctuations offered earlier is applied to its realization. This method allows to describe and assign analytically in computer calculations the structure of the medium filled with inclusions. On the basis of the  turbulent flow with more simple laminar flow with fluctuations, simulating the «vortex backfill». The calculated model of «vortex backfill» is constructed, allowing to calculate and analyze turbulent flow in pipes.